Buying for Britain, China, or India? Patriotic trade, ethnicity, and market in the 1930s British empire/Commonwealth*. Issue 3 (18th October 2017) - Thackeray, David
Abstract: This article seeks to gain a clearer understanding of the language, reach, and limits of competing patriotic trade campaigns in the British empire during the 1930s, focusing on efforts to promote the purchase of Indian, Chinese, and 'British' products (a term which was used to refer to goods from both the UK and the Dominions). Civil society groups used patriotic-buying campaigns to promote and maintain forms of regionalized integration in response to the partial deglobalization of trade. Supporters of such campaigns sought to develop trade networks based on ethnic ties which could connect across and, in the Chinese case, beyond imperial spaces. However, the hybridity of colonial subjects' identities impeded each of these efforts to develop patriotic trade networks and meant that the content, character, and popular appeal of trade campaigns shifted between different regions.